Establishment of a mortality risk nomogram for predicting in-hospital mortality of sepsis: cohort study from a Chinese single center - Wu, Hongsheng; Jia, Shichao; Liao, Biling; Ji, Tengfei; Huang, Jianbin; Luo, Yumei; Cao, Tiansheng; Ma, Keqiang (Frontiers in Medicine, 2024)
Objective: To establish a mortality risk nomogram for predicting in-hospital mortality of sepsis patients in the Chinese population. Methods: Data were obtained from the medical records of sepsis patients enrolled at the Affiliated Huadu Hospital, Southern Medical University, between 2019 and 2021. A total of 696 sepsis patients were initially included in our research, and 582 cases were finally enrolled after screening and divided into the survival group (n=400) and the nonsurvival group (n=182) according to the incidence of mortality during hospitalization. Twenty-eight potential sepsis-related risk factors for mortality were identified. Least absolute shrinkage and selection operator (LASSO) regression was used to optimize variable selection by running cyclic coordinate descent with k-fold (tenfold in this case) cross-validation. We used binary logistic regression to build a model for predicting mortality from the variables based on LASSO regression selection. Binary logistic regression was used to establish a nomogram based on independent mortality risk factors. To validate the prediction accuracy of the nomogram, receiver operating characteristic curve (ROC) analysis, decision curve analysis (DCA) and restricted cubic spline (RCS) analysis were employed. Eventually, the Hosmer-Lemeshow test and calibration curve were used for nomogram calibration. Results: LASSO regression identified a total of ten factors, namely, CHD, LYMP, NLR, RDW, CRP, PCT, lactic acid, PT, ALT, Tbil, IL6, that were incorporated into the multivariable analysis.The ROC curves in the training and validation sets were 0.9836 and 0.9502, respectively. DCA showed that the nomogram could be applied clinically if the risk threshold was between 29.52% and 99.61% in the training set and between 31.32% and 98.49% in the testing set. RCS showed that when the value of independent risk factors from the predicted model exceeded the median, the mortality hazard ratio increased sharply. The results of the Hosmer-Lemeshow test ( 2 =0.1901, df=2, P=0.9091) and the calibration curves of the training and validation sets showed good agreement with the actual results, which indicated good stability of the model. Conclusion: Our nomogram, including CHD, LYMP, NLR, RDW, lactic acid, PT, CRP, PCT, Tbil, ALT, and IL6, exhibits good performance for predicting mortality risk in adult sepsis patients.